2005
DOI: 10.1007/s00018-005-5015-5
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanism of actomyosin-based motility

Abstract: Sophisticated molecular genetic, biochemical and biophysical studies have been used to probe the molecular mechanism of actomyosin-based motility. Recent solution measurements, high-resolution structures of recombinant myosin motor domains, and lower resolution structures of the complex formed by filamentous actin and the myosin motor domain provide detailed insights into the mechanism of chemomechanical coupling in the actomyosin system. They show how small conformational changes are amplified by a lever-arm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
88
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(94 citation statements)
references
References 123 publications
1
88
5
Order By: Relevance
“…The blocked head is shown in yellow with the amino acids framing loop 2 shown in magenta, although the actual residues of loop 2 are missing. The remaining residues of the approximate actin-binding interface have been colored in dark green (37). (Inset) Magnification of the interaction after a clockwise 90°rotation around the coiled-coil main axis.…”
Section: Methodsmentioning
confidence: 99%
“…The blocked head is shown in yellow with the amino acids framing loop 2 shown in magenta, although the actual residues of loop 2 are missing. The remaining residues of the approximate actin-binding interface have been colored in dark green (37). (Inset) Magnification of the interaction after a clockwise 90°rotation around the coiled-coil main axis.…”
Section: Methodsmentioning
confidence: 99%
“…In the weakly bound transition state, when a leading head is searching for a new binding site on actin to continue forward motion, loop 2 maintains contact with actin and appears to act as a tether (16) (Fig. 1).Increasing the net positive charge of loop 2 increases the affinity of myosin for actin (14,(17)(18)(19). We previously showed that replacing loop 2 of mouse myosin V (net loop charge of ϩ5) with the corresponding loop from a yeast class V myosin (Myo4p, net loop charge of 0) caused a dramatic reduction in processive run lengths, especially at high ionic strength (20).…”
mentioning
confidence: 99%
“…2) that lies inside one of the ATP-binding site to the actin molecule, found at the subdomain 3. This amino acid substitution can influence the actin's affinity for ATP, a feature that has been described in actin isoforms of some vertebrate species, including fish, and in Sacharomyces cervisae, a yeast that has one essential actin gene that encodes a protein that shares a high identity degree (87%) to vertebrate skeletal muscle actins (Geeves et al 2005, Mercer et al 2011. Similarly, it has been evidenced that a Ser/Ala substitution at the amino acid 14, at the actin subdomain 1, results in a 40 to 60-fold decrease in actin's affinity for ATP (Chen et al 1995), since Alanine has a lower hydrogen bonding capacity.…”
Section: Discussionmentioning
confidence: 99%